Violence against women and justice from women in the Amazon - Justo Nieto, Milena (2020)
This his paper analyzes the new forms of violence against women that are unleashed in the Amazon, in a context of extractivism and exploitation. Through secondary sources, the relationship between the precariousness of life and the resurgence of forms of violence against women and against everything feminized is studied: the body of women, nature, culture. One of the forms of violence that is identified is unleashed in the Amazon, is the institutional violence against women, referred to the violence of the justice system and the State when it is permissible in the face of impunity and indifference to the cases raised in this area , which carry greater barriers to access justice. From this, a theoretical proposal is introduced in relation to women’s responses to the impunity of cases of violence against them and the precariousness of life, which is based on emancipatory legal pluralism. The development of an agency of women in the face of the crisis is postulated, manifestations of resilience that can become ways of doing justice from social practices, in this case from the practices of women in the Amazon.